2020
DOI: 10.1038/s42004-020-0290-5
|View full text |Cite
|
Sign up to set email alerts
|

A human protein hydroxylase that accepts D-residues

Abstract: Factor inhibiting hypoxia-inducible factor (FIH) is a 2-oxoglutarate-dependent protein hydroxylase that catalyses C3 hydroxylations of protein residues. We report FIH can accept (D)- and (L)-residues for hydroxylation. The substrate selectivity of FIH differs for (D) and (L) epimers, e.g., (D)- but not (L)-allylglycine, and conversely (L)- but not (D)-aspartate, undergo monohydroxylation, in the tested sequence context. The (L)-Leu-containing substrate undergoes FIH-catalysed monohydroxylation, whereas (D)-Leu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 51 publications
0
17
0
Order By: Relevance
“…Movement of the Tyr102 FIH sidechain has been previously observed in crystal structures of FIH complexed with different substrates (Supplementary Fig. 33) 43 . In agreement with the proposal that the coordination of ( S )- 11 and ( S )- 18 to the FIH active site impairs substrate binding, FIH crystals with both inhibitor and substrate-bound could not be obtained.…”
Section: Resultsmentioning
confidence: 52%
See 1 more Smart Citation
“…Movement of the Tyr102 FIH sidechain has been previously observed in crystal structures of FIH complexed with different substrates (Supplementary Fig. 33) 43 . In agreement with the proposal that the coordination of ( S )- 11 and ( S )- 18 to the FIH active site impairs substrate binding, FIH crystals with both inhibitor and substrate-bound could not be obtained.…”
Section: Resultsmentioning
confidence: 52%
“…The current evidence suggests that FIH is biochemically more promiscuous with respect to its substrate requirements than AspH as it also catalyzes the hydroxylation of residues other than Asp and Asn (Fig. 1b ) 41 43 .…”
Section: Introductionmentioning
confidence: 80%
“…Interestingly, the yeast homolog of human OGFOD1 is reported to catalyze both the single and apparent double hydroxylation of the analogous prolyl residue ( 30 ). In the case of substrate analog studies with isolated FIH, we have also observed that the double hydroxylation of a single residue can occur ( d -Leu) though there is no evidence that this reaction is of biological relevance ( 27 ). Evidence that FIH can catalyze the desaturation of certain residues has also been accrued ( 17 ).…”
Section: Discussionmentioning
confidence: 92%
“…However, certain 2OG-dependent protein hydroxylases, including FIH, AspH, JMJD6 and some procollagen-modifying enzymes, likely act on multiple substrates ( 24 , 25 ). FIH is of particular interest because not only can it accept both HIF-α isoforms and multiple ARD (and other) proteins but also it can accept different residues as substrates, including Asn, Asp, His, and, at least in isolated form, some D-amino acids ( 17 , 18 , 26 , 27 ) at least in the context of ARD-derived substrates.…”
Section: Discussionmentioning
confidence: 99%
“…These broad-spectrum inhibitors show distinct selectivity profiles; for example, 2,4-PDCA efficiently inhibits AspH and some JmjC KDMs [ 14 , 15 ]. By contrast, 2,4-PDCA is only a weak inhibitor of the PHDs and of FIH [15] , which catalyzes the stereoselective C3 hydroxylation of Asn/Asp/His/Ser/Leu-residues (Supporting Figure S1) [ 16 , 17 ]. For other classes of human 2OG oxygenases, such as the ribosomal oxygenase 2 (RIOX2; MYC-induced nuclear antigen 53, MINA53), which catalyzes the stereoselective C3 hydroxylation of His39 of the 60S ribosomal protein L27a (RPL27A) [18] , the potency of these broad-spectrum inhibitors has not been reported.…”
Section: Introductionmentioning
confidence: 99%